A network meta-analysis of updated haemostatic strategies for hysterectomy. (November 2016) - Guo, Tao; Ren, Liang; Wang, Quanxiong; Li, Kun
Abstract: Objective: To determine the best haemostatic strategy for hysterectomy through a network meta-analysis. Methods: We conducted a systematic literature search of the PubMed, Embase, and Cochrane Library databases and extracted data from randomized controlled trials comparing haemostatic strategies for hysterectomy. Direct comparisons and network meta-analyses were conducted in RevMan and ADDIS. Consistency models were established to identify the differences among different haemostatic strategies, and cumulative probability was used to rank the included strategies. Inconsistencies were also tested using node-splitting models. Results: Twenty studies from 16 articles (2 articles contained 3 studies each) comprising 1392 patients were included. Direct meta-analysis showed that the LigaSure (SMD = −1.42 [−2.39,  −0.44], P = 0.004), bipolar vessel sealing systems (BVSS) (SMD = −0.35 [−0.66,  −0.03], P = 0.03), and pituitrin (SMD = −2.13 [−4.14,  −0.13], P = 0.04) applications were effective haemostatic strategies. Based on the network meta-analysis and related subgroup analysis of different surgical procedures, the results showed that the application of pituitrin seemed to be the best haemostatic method for hysterectomy (Rank P = 0.64), especially for vaginal hysterectomy (Rank P = 0.72). The application of LigaSure was the best strategy for abdominal hysterectomy (Rank P = 0.54) but was not effective for laparoscopic hysterectomy (direct comparison with BVSS, MD = −31.39 [−146.61, 83.83], P = 0.59). The node-splitting models test revealed that no significant inconsistencies existed in this research. Conclusions: Pituitrin application seemed to be the most effective haemostatic strategy for hysterectomy and was especially suitable for vaginal hysterectomy. The best method for reducing blood loss in abdominal hysterectomy was the application of LigaSure. Highlights: A comprehensive literature review and quantitative analysis were conducted. The best related hemostatic strategies for hysterectomy were determined. This article provided evidence-based suggestions for clinical decision-making.